2021
DOI: 10.1016/j.ymssp.2020.107059
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the spectrum of leak noise in buried plastic water distribution pipes using acoustic or vibration measurements remote from the leak

Abstract: An appropriate model of leak noise at source is necessary in analytical and numerical approaches to investigate the characteristics of leak noise measured remotely from the leak in buried water pipes. It is extremely difficult to measure leak noise at source in practice, so an inverse method is needed to predict this from measurements made either side of the leak at convenient access points. This paper presents such a method, and illustrates the approach using four data sets from three different test sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This denotes that y 2 has a wider frequency bandwidth than y 1 . Therefore, we can infer from the previous leak theory (Diao et al 2020;Scussel et al 2021) that the randomness of the leak signal is often greater than that of other stable noise signals, except white noise, implying that the bandwidth of the leak source signal is wider than other noise signals. Consequently, we concluded that y 2 was the leak source signal obtained by separation algorithm, and y 1 was the branch noise.…”
Section: Conditions Of the Experimentsmentioning
confidence: 90%
“…This denotes that y 2 has a wider frequency bandwidth than y 1 . Therefore, we can infer from the previous leak theory (Diao et al 2020;Scussel et al 2021) that the randomness of the leak signal is often greater than that of other stable noise signals, except white noise, implying that the bandwidth of the leak source signal is wider than other noise signals. Consequently, we concluded that y 2 was the leak source signal obtained by separation algorithm, and y 1 was the branch noise.…”
Section: Conditions Of the Experimentsmentioning
confidence: 90%
“…Accelerometers are more convenient as they can be attached to the fitting's outer wall, whereas hydrophones must be immersed in water. However, hydrophones have a higher signal-to-noise ratio and can measure both vibration and pressure for locating and sizing the leak, respectively, whereas accelerometers only measure vibration [46]. The sensors' data are fed to a correlator to calculate the time lag.…”
Section: A Sound Wave Methodsmentioning
confidence: 99%
“…Several experiments with a test rig located in Ottaw in Canada showed the prospects of this technique [41]- [46]. The authors of that study conducted experiments on a 200m test rig with buried PVC pipes with a 75-mm diameter.…”
Section: A Sound Wave Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, an increasing number of technologies for leak detection and location have been used, which can be generally divided into hardware-based and softwarebased methods, such as the volume balance method [3], negative pressure wave method [4], fiber Bragg grating sensor method [5], acoustic method [6,7] etc. Different technologies have their characteristics, advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%